Pembuatan Pojok Baca dan Dekorasi Ruang sebagai Upaya Meningkatkan Minat Baca Anak Usia Dini - Eunike Milasari Listyaningrum; Angelia Christina; Nurhana Oktaviani; Renyta Arum Anggraini; Linda Rahmaningtyas (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Nowadays, the development of technology for early childhood is growing so rapidly that children's interest in reading books is decreasing. In addition to the family, schools become the second environment for children so it is hoped that schools become a place where children develop an interest in reading and with a pleasant atmosphere. The reading corner is a solution for children to be able to develop their interest in reading and attractive decorations will make children excited in developing their literacy. This community service research uses a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation. This research was conducted at Kristen 2 Salatiga Kindergarten. The purpose of this research is to increase children's interest in reading and make the learning atmosphere comfortable and fun. The result of this community service activity is that it can create a new and fun learning atmosphere for students and increase interest in reading for early childhood so as to increase knowledge for children.